Responding to coercive control in criminal justice domestic violence perpetrator programmes in England and Wales: Conceptual, operational, and methodological complexities - Renehan, Nicole (Probation journal, 2023)
Evaluations of domestic violence perpetrator programmes have not produced evidence that they are as effective at reducing male, non-violent, coercively controlling behaviours. This article proposes such limitations are understood by adopting a more complex conceptualisation of coercive control for which the reasons are both gendered and biographically unique. Drawing on document analyses and in-depth interviews with eight programme facilitators and an in-depth case study of one male participant, this article explores the merits and limitations of the cognitive behavioural, skills-based criminal justice programme, Building Better Relationships, in addressing coercively controlling behaviours. The dual (re)conceptualisation of coercive control proposed has implications for both practice and programme evaluation methods.